2019
DOI: 10.1086/702848
|View full text |Cite
|
Sign up to set email alerts
|

Condition-Dependent Begging Elicits Increased Parental Investment in a Wild Bird Population

Abstract: The coevolution of parental supply and offspring demand has long been thought to involve offspring need driving begging and parental care, leaving other hypotheses underexplored. In a population of wild birds, we tested experimentally whether begging serves as a negatively condition-dependent signal of need or a positively condition-dependent signal of quality. Across multiple years, we food-supplemented nestling house wrens shortly after hatching, and simultaneously manipulated corticosterone levels to simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 102 publications
0
11
0
Order By: Relevance
“…Explanations for juveniles begging for food have centred around begging being an honest signal of hunger ( Bowers et al, 2019 ; Kilner & Johnstone, 1997 ; Godfray, 1991 ; Mock & Parker, 1997 ) and competition between siblings ( Harper, 1986 ; Stamps, Metcalf & Krishnan, 1978 ; Macnair & Parker, 1979 ; Parker, 1985 ). According to the honest signalling hypothesis ( Bowers et al, 2019 ; Kilner & Johnstone, 1997 ; Godfray, 1991 ; Mock & Parker, 1997 ), the costly qualities of extravagant begging behaviours advertise an offspring’s current nutritional need ( Cotton, Kacelnik & Wright, 1996 ; Kilner, 1995 ; Kilner & Johnstone, 1997 ; Ottoson, 1997 ). However, this idea remains somewhat controversial ( Mock, Dugas & Strickler, 2011 ; Parker, Royle & Hartley, 2002 ), and others have argued that stronger, rather than hungrier, individuals can maintain higher and longer levels of begging ( Grafen, 1990 ; Parker, Royle & Hartley, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Explanations for juveniles begging for food have centred around begging being an honest signal of hunger ( Bowers et al, 2019 ; Kilner & Johnstone, 1997 ; Godfray, 1991 ; Mock & Parker, 1997 ) and competition between siblings ( Harper, 1986 ; Stamps, Metcalf & Krishnan, 1978 ; Macnair & Parker, 1979 ; Parker, 1985 ). According to the honest signalling hypothesis ( Bowers et al, 2019 ; Kilner & Johnstone, 1997 ; Godfray, 1991 ; Mock & Parker, 1997 ), the costly qualities of extravagant begging behaviours advertise an offspring’s current nutritional need ( Cotton, Kacelnik & Wright, 1996 ; Kilner, 1995 ; Kilner & Johnstone, 1997 ; Ottoson, 1997 ). However, this idea remains somewhat controversial ( Mock, Dugas & Strickler, 2011 ; Parker, Royle & Hartley, 2002 ), and others have argued that stronger, rather than hungrier, individuals can maintain higher and longer levels of begging ( Grafen, 1990 ; Parker, Royle & Hartley, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical models of begging have focussed on the nutritional demands of offspring and food solicitation interactions with their parents ( Grafen, 1990 ; Zahavi, 1975 ). These models, and empirical evidence, support two main explanations for begging: an ‘honest signal of hunger’ ( Bowers et al, 2019 ; Kilner & Johnstone, 1997 ; Godfray, 1991 ; Godfray, 1995 ; Mock & Parker, 1997 ), which is most commonly tested in young birds (e.g., Capodeanu-Nägler et al, 2017 ; Christe, Richner & Oppliger, 1996 ; Karasov & Wright, 2002 ), and competition between siblings for the acquisition of food from parents, known as the ‘sibling scramble hypothesis’ ( Harper, 1986 ; Stamps, Metcalf & Krishnan, 1978 ; Macnair & Parker, 1979 ; Parker, 1985 ). As begging and the resultant food sharing are typically documented to occur between kin, these interactions can be explained by inclusive fitness benefits ( Hamilton, 1964 ).…”
Section: Introductionmentioning
confidence: 87%
“…More recent studies in wrens have shown that experimentally foodsupplemented nestlings (nestlings in better condition) begged more intensely for food than nestlings that were not supplemented. Parents responded to the more intense begging signals of the nestlings in better condition, increasing their provisioning rate to them, but not to the offspring in poorer condition (Bowers et al 2019). And in tadpoles, begging effort and performance were higher in more developed and higher condition tadpoles and actually declined with food deprivation (Dugas et al 2017).…”
Section: Models Of Honest Beggingmentioning
confidence: 97%
“…The life history traits of offspring are of interest to study because they reflect broods' reproductive value and needs. Because parents' caring efforts are linked to the trade-off between their current and future reproductive fitness, they are expected to invest more in broods of higher reproductive value [8,9,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%